Analysis of Avtur Fuel Usage in Aircraft with an IT Governance-Based Simulation Approach Using the COBIT Model - Wiko Pratama; Leni Marlina; Rian Farta Wijaya (Jurnal Informasi dan Teknologi, 2025)
The management of the use of aviation fuel in aircraft is a crucial aspect in the aviation industry, which has a direct impact on operational efficiency and environmental sustainability. This study aims to analyze the use of avtur fuel with an IT Governance-based simulation approach using the Control Objectives for Information and Related Technologies model or abbreviated as COBIT. The COBIT model was chosen for its ability to manage structured information technology governance, so that it can help in optimizing decision-making related to fuel efficiency. The simulations carried out in this study involve various operational scenarios to evaluate the effectiveness of avtur management by utilizing key performance indicators (KPIs) in the COBIT framework. The results of the analysis show that the implementation of COBIT-based IT Governance can improve the efficiency of audit use by improving monitoring, risk management, and data-based decision-making processes. These findings contribute to the development of fuel efficiency strategies in the aviation industry and open up opportunities for the application of similar models in other transportation sectors.